Aksi Bergizi Bebas Anemia Untuk Meningkatkan Pengetahuan Siswi Di SMP Progresif Bumi Sholawat Sidoarjo - Choirul Anna Nur Afifah; Rita Ismawati; Lini Anisfatus Sholihah (CV. Multi Kreasi Media, 2023)
Adolescence is a transition period between children and adults. Nutritional needs that are not properly met result in delayed sexual maturation or the emergence of anemia. The nutritional action that will be provided will be in the form of nutritional education and giving iron tablets to students. The aim of the activity is to increase knowledge about the nutritional needs of adolescents, anemia and preventing anemia. The nutritional action was carried out on 26 class VII students at SMP Progresif Bumi Sholawat. Implementation of activities consists of: the preparation stage, namely the formulation and development of material, preparation of educational equipment; the implementation stage consists of providing nutritional education to female students with the UNO block game; The evaluation stage is in the form of a pretest-posttest on nutritional knowledge and filling out a questionnaire responding to the implementation of activities. Delivery of material using UNO block games, and discussions. All participants (100%) participated in the activity completely from start to finish. The average ability of participants in mastering the material can be said to be quite good with an increase in the average score from pretest to posttest of 8.08 points. The results of filling in the participant response questionnaire revealed that the indicators of suitability of the material, media and instructor's abilities were rated positively (strongly agree-agree) by the majority of participants with a range of 70-100% of participants. The joint consumption of iron tablets was welcomed very enthusiastically by all the students of SMP Progresif Bumi Sholawat.